Productivity and economics of carrot (Daucus carota) as influenced by interactive effect of potassium and micronutrients - CHOUDHARY, GULAB; GARHWAL, O P; BAIRWA, L N; MEENA, K K; NETWAL, MANJU (The Indian Journal of Agricultural Sciences, 2024)
Deficiency and insufficient nutrients application are the major factor responsible to reduced carrot root yield. Nutrients in balanced amount are critical aspect for getting optimal root yield for a particular agro-climatic condition. An appropriate nutrient management including potassium and micronutrients might rise and improve the productivity of carrot. The experiment was conducted at Sri Karan Narendra Agriculture University, Jobner, Jaipur, Rajasthan to study the effect of variable potassium and micronutrients formulations on performance of carrot. Results were found to be significant for the yield attributes, yield and economics of carrot. Soil application of potassium (MOP) @150 kg/ ha significantly enhanced the average root weight (189.3 g), root diameter (3.7 cm), shoot: root ratio (0.5), edible root length (23.7 cm), root yield (28.3 t/ha), net returns (₹205161/ha) and B:C ratio (2.7) of carrot. Among the micronutrients formulations, significantly higher average root weight (182.8 g), root diameter (3.7 cm), shoot: root ratio (0.5), edible root length (24.2 cm), root yield (27.8 t/ha), net returns (₹202576/ha) and B:C ratio (2.7) were noticed in foliar application of ZnSO4 @0.5%. Results of interaction shown that soil application of potassium (MOP) @150 kg/ha and ZnSO4 @0.5% significantly better in the average root weight (209.6 g), root yield (31.4 t/ha), net returns (₹2,35,918/ha) and B:C ratio (3.03).